2009
DOI: 10.1097/ncc.0b013e3181a4802c
|View full text |Cite
|
Sign up to set email alerts
|

Exploring the Feasibility of a Therapeutic Music Video Intervention in Adolescents and Young Adults During Stem-Cell Transplantation

Abstract: The purpose of this study was to explore the feasibility and preliminary efficacy of a therapeutic music video (TMV) intervention for adolescents and young adults (AYAs) undergoing stem-cell transplantation (SCT). Twelve AYAs (aged 11-24 years) were randomized to the TMV or an audio-book protocol. The TMV was designed to diminish symptom distress and improve coping, derived meaning, resilience, and quality of life by supporting AYAs in exploring thoughts and feelings. Six sessions with a board-certified music … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
80
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(80 citation statements)
references
References 17 publications
(24 reference statements)
0
80
0
Order By: Relevance
“…The control group listened to self-chosen audio books and afterwards discussed the impressions and thoughts about the book content with a therapist. Burns et al [40] report a good consent rate of 63% which indicates a good feasibility of the TMV. A trend for an increased quality of life was observed in the intervention group.…”
Section: Technology-based Interventionsmentioning
confidence: 94%
See 2 more Smart Citations
“…The control group listened to self-chosen audio books and afterwards discussed the impressions and thoughts about the book content with a therapist. Burns et al [40] report a good consent rate of 63% which indicates a good feasibility of the TMV. A trend for an increased quality of life was observed in the intervention group.…”
Section: Technology-based Interventionsmentioning
confidence: 94%
“…Burns et al [40] assessed the feasibility of a therapeutic music video intervention (TMV) based on the Resilience in Illness Model (RIM; formerly called Adolescent Resilience Model ARM) developed by Haase et al [45,46]. Participants were randomized into an intervention and a control group.…”
Section: Technology-based Interventionsmentioning
confidence: 99%
See 1 more Smart Citation
“…The level of enthusiasm of the study team was reflected in their involvement in multiple dissemination efforts, including presentations, published abstracts, and manuscripts [10–22]. These efforts afforded team members opportunities to participate in dissemination, a new and exciting opportunity for many of the participating nurses that was also celebrated at each of the data collection sites.…”
Section: Strategiesmentioning
confidence: 99%
“…Two people aged 30 and 24 years who had cancer reported that "hard and heavy metal" music purged their anger and enabled "ideal self" expression [11]. Music therapy 1 methods improved adolescent cancer patients' selfesteem [13] and stress management [14], and therapeutic music video (TMV) interventions during stem cell transplant produced favourable effects in AYAs' spirituality, confidence/ mastery, hope, and self-transcendence [15]. AYA parents were also grateful for TMV's perceived benefits [16].…”
Section: Introductionmentioning
confidence: 99%